UTILIZATION OF ROCURONIUM AT A DOSE OF 0.8 MG/KG BODY WEIGHT IN CESAREAN SECTION WITH SPHENOID WING MENINGIOMA: A CASE REPORT - Salmon, Deni; Senapathi, Tjokorda Gede Agung; Pradhana, Adinda Putra; Hartawan, IGAG Utara (HEARTY, 2025)
Sphenoid Wing Meningioma (SWMNG) is a prevalent intracranial tumor with significant implications for obstetric patients, particularly due to heightened risks of cerebral edema and increased intracranial pressure (ICP). This case highlights the anesthetic management of a pregnant patient with SWMNG and symptomatic epilepsy, focusing on the use of rocuronium bromide for rapid sequence intubation (RSI). Rocuronium, a non-depolarizing neuromuscular blocker, offers rapid onset and intermediate duration, making it a preferred choice for high-risk cases. A 34 year old woman at 38 weeks and 5 days of gestation with a confirmed diagnosis of SWMNG and symptomatic epilepsy underwent a cesarean section and surgical sterilization. The patient’s clinical history included frequent transient loss of awareness episodes, exacerbated during pregnancy. Imaging confirmed SWMNG, necessitating general anesthesia (GA) with rocuronium at a dose of 0.8 mg/kg to ensure effective RSI while minimizing risks of prolonged neuromuscular blockade, compromised hemodynamic stability, and increased ICP. The procedure was successfully completed with stable maternal and fetal outcomes. Rocuronium facilitated optimal intubation conditions and muscle relaxation, with minimal placental transfer and preserved uterine contractility. This case underscores the efficacy of precise rocuronium dosing in balancing rapid recovery, safety, and the unique challenges of airway management in obstetric patients with intracranial tumors. Vigilant monitoring and tailored anesthetic strategies are essential to mitigate complications, ensuring favorable outcomes for both mother and fetus.